Is Rheumatoid Arthritis a Cardiovascular Risk‐Equivalent to Diabetes Mellitus?. Issue 11 (26th October 2018) - Curtis, Jeffrey R.; Yang, Shuo; Singh, Jasvinder A.; Xie, Fenglong; Chen, Lang; Yun, Huifeng; Muntner, Paul; Kent, Shia T.; Levitan, Emily B.; Safford, Monika M.; Saag, Kenneth G.; Zhang, Jie
Abstract : Objective: The 2013 American College of Cardiology/American Heart Association cholesterol treatment guidelines recommend statins for patients with diabetes mellitus ages 40–75 years due to their elevated cardiovascular disease (CVD) risk. We compared the incidence of hospitalized acute myocardial infarction (MI), stroke, and coronary revascularization according to whether patients had diabetes mellitus, rheumatoid arthritis (RA), both, or neither. Methods: Using 2006–2010 private and public health plan claims, we identified 4 mutually exclusive retrospective cohorts ages >40 years: patients with RA and diabetes mellitus, RA only, diabetes mellitus only, or neither condition. Patients with prevalent CVD were excluded. Outcomes included acute MI and stroke, identified from inpatient discharge diagnosis codes, and coronary revascularization from procedure codes. Across the 4 cohorts, we calculated incidence rates (IRs) of the outcomes, standardized to the 2010 US census age and sex distribution. Results: We identified 920, 772 eligible participants. The age‐ and sex‐standardized IRs (per 1, 000 person‐years) for MI were highest among patients with RA and diabetes mellitus (IR 12.6 [95% confidence interval (95% CI) 10.7–14.7]), followed by patients with diabetes mellitus only (IR 10.7 [95% CI 10.3–11.0]), RA only (IR 5.7 [95% CI 5.2–6.3]), and with neither condition (IR 4.2 [95% CI 4.1–4.3]). Conclusion: Findings from the present study suggest that while CVD risk in RA is elevated, it is lower in magnitude compared to the CVD risk associated with diabetes mellitus. Therefore, considering RA a diabetes mellitus risk‐equivalent with respect to hyperlipidemia management may not be appropriate.